Pre-service teachers' views on using English comics to improve pupils' English language skills - Najihah Pazaer; Aladdin Assaiqeli (Studies in English Language and Education, 2023)
This paper highlights the ESL pre-service elementary school teachers’ views on using English comics in the classroom and using English comics to assist elementary school pupils in improving their English language skills. A descriptive survey research design was used, and a quantitative method study was done among 64 pre-service teachers utilising an internet questionnaire as an instrument aimed to answer questions concerning their views towards the use of English comics as a medium for teaching and learning English and the effectiveness in improving pupils’ English language abilities. The results from the questionnaire were analysed quantitatively, and the findings were summarised using descriptive statistics and frequency count to characterise the properties of the large group of samples. From the survey, it was found that most pre-service teachers have positive perceptions of using comic books as teaching and learning tools in class. Furthermore, the findings indicated that the pre-service teachers believe it is advantageous to improving students’ English language abilities. The study offers other recommendations for future research and implications that might help ESL instructors and young students enhance their students’ English language proficiency.